Aseptic Loosening Rates in Distal Femoral Endoprostheses: Does Stem Size Matter? - Bergin, Patrick F. (Springer-Verlag, 2011)
BACKGROUND: Long-term survival of distal femoral endoprosthetic replacements is largely affected by aseptic loosening. It is unclear whether and to what degree surgical technique and component selection influence the risk of loosening. QUESTIONS/PURPOSES: We (1) established the overall failure and aseptic loosening rates in a tumor population and asked (2) whether stem diameter and specifically the diaphysis-to-stem ratio predicts loosening, and (3) whether resection percentage correlates with failure. METHODS: We retrospectively reviewed the charts of all 93 patients in whom 104 distal femoral replacements had been performed from 1985 to 2008. We extracted the following data: age, need for revision surgeries, tumor diagnosis, adjunct treatment, and implant characteristics. We reviewed radiographs and determined stem size, bone diaphyseal width, and resection percentage of the femur. Kaplan-Meier survivorship was calculated for all implant failures and failures resulting from aseptic loosening. We evaluated radiolucent lines in patients with radiographic followup over 5 years. We identified independent risk factors for loosening. The minimum followup for radiographic evaluation was 5 years (mean, 12.7 years; range, 5.4–23.5 years). RESULTS: Overall implant survival for 104 stems in 93 patients was 73.3% at 10 years, 62.8% at 15 years, and 46.1% at 20 years. Survival from aseptic loosening was 94.6% at 10 and 15 years and 86.5% at 20 years. Of the variables analyzed, only bone:stem ratio independently predicted aseptic failure. Patients with stable implants had larger stem sizes and lower bone:stem ratios than those with loose implants (14.5 mm versus 10.7 mm and 2.02 versus 2.81, respectively). CONCLUSIONS: Our data suggest durability relates to selecting stems that fill the canal. LEVEL OF EVIDENCE: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.